2016
DOI: 10.1002/jcb.25490
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Flavonoid Fisetin Causes Cell Cycle Arrest, Caspase‐Dependent Apoptosis, and Enhanced Cytotoxicity of Chemotherapeutic Drugs in Triple‐Negative Breast Cancer Cells

Abstract: Fisetin (3,3',4',7-tetrahydroxyflavone), a flavonoid found in a number of fruits and vegetables, has diverse biological activities, including cytotoxic effects on cancer cells. In this study, we investigated the effect of fisetin on triple-negative breast cancer (TNBC) cells. TNBC has a poorer prognosis than other types of breast cancer and treatment options for this disease are limited. Fisetin inhibited the growth of MDA-MB-468 and MDA-MB-231 TNBC cells, as well as their ability to form colonies, without sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 43 publications
7
56
0
Order By: Relevance
“…It also inhibits micro-ophthalmia associated transcription factor (MITF) in melanoma cells and inhibits invasion of melanoma cells via modulation of the MAPK and NF-κB pathways [20–22]. Recently, it was reported that fisetin causes cell cycle arrest, apoptosis (caspase-dependent), and potentiate the anti-tumor effect of Chemotherapeutics in triple-negative breast cancer cells [23]. …”
Section: Introductionmentioning
confidence: 99%
“…It also inhibits micro-ophthalmia associated transcription factor (MITF) in melanoma cells and inhibits invasion of melanoma cells via modulation of the MAPK and NF-κB pathways [20–22]. Recently, it was reported that fisetin causes cell cycle arrest, apoptosis (caspase-dependent), and potentiate the anti-tumor effect of Chemotherapeutics in triple-negative breast cancer cells [23]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, Fisetin inhibited MDA-MB-468 and MDA-MB-231 cell's division and induced apoptosis involving mitochondrial membrane depolarization and activation of caspase-9 and caspase-8, as well as cleavage of PARP 1 [12]. Similarly, quercetin, another flavonoid compound also causees loss of membrane potential and activation of caspase cascade and PARP cleavage.…”
Section: Commentarymentioning
confidence: 99%
“…On the other hand, different studies determined G2/M phase arrest in MDA-MB-468 and MDA-MB-231 cells in response to fisetin and genistein treatments [12,19]. Results from another study suggesting that genistein-induced G2/M cell cycle arrest in MDA-MB-231 cells by modulating Ras/ MAPK/AP-1 cancer signaling pathway [20].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Live cells remained adhered to the plate and dead cells were washed away (Smith et al, 2016, Chiba et al, 1998. Three replicate plates were performed for cell count using crystal violet assay, each plate included 6 technical replicate wells per treatment.…”
Section: Crystal Violet Assaymentioning
confidence: 99%